Behavior of Nano Block Retaining Walls Reinforced with GFRP Bars - Bubpi, Attaphol; Sirisriphet, Yongyuth; Amornpinyo, Prach; Tho-In, Tawatchai; Yodsiri, Pakaphorn; Poungchompu, Pongsagorn (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
This paper presented the results of 4 types nano block retaining walls. They were divided into non-reinforced and reinforced GFRP with diameters of 6, 9 and 12 mm with tensile strength of 30 lb. Nano block retaining walls with dimensions of 1.62 meters high, 2.00 meters wide, 0.20 meters thickness were used to study their horizontal movement behavior. The results of the experiment showed that nano block retaining walls reinforced with GFRP had better resistance to horizontal movement than non-reinforced retaining walls. At the same time, nano block retaining wall reinforced with GFRP with tensile strength of 30 lb with dimensions of 6, 9 and 12 mm had average maximum values of horizontal displacement of 2.43, 3.40 and 4.37 mm, respectively.